Parental bonding and parent-child relationship among tertiary students - Tam, Cai Lian *; Yeoh, Si Han * (Sunway University College, 2008)
Parental bonding is an important predictor that gives a lot of insight into parent-child relationship. Studies have demonstrated the importance of parent child relationship for adjustment, ranging from attachment during infancy, indiscipline style during childhood and adolescence to parenting style during adulthood. This paper aims to investigate the relationship between parental bonding and parent-child relationship among tertiary level students in which gender and cultural effects were also taken into consideration. A survey with two valid inventories?Parental Bonding Inventory (PBI) and Parent-Child Relationship Survey (PCRS) was carried out on 160 tertiary level students from Selangor. Results indicate that stronger parental bonding promotes better parent-child relationship. Besides, females were found to have better parental bonding as well as parent-child relationship compared to males. From a cultural aspect, there is no difference among races in terms of parental bonding and parent-child relationship.